PENGARUH PENGGUNAAN KEY OPINION LEADER TASYA FARASYA TERHADAP MINAT BELI PRODUK KECANTIKAN GENERASI Z DI WILAYAH KOTA BANDUNG - Nadia Rizky Vindiazhari (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2024)
Key Opinion Leader (KOL), Tasya Farasya, is becoming an important strategy in influencing the purchasing decision of the beauty products industry for Generation Z in the Bandung City Area. Through the regression test method, it produced an R Square of 74.3%, which indicates that around 74.3% of the influence of KOL Tasya Farasya on buying interest of Generation Z beauty products in the Bandung City Area. Keywords: Key Opinion Leadr (KOL), Buying Interest, Generation Z